Calculating moisture emissivity of timber members with different surface treatment. (1st February 2021) - Zhang, Zhongwen; He, Zhili; Xu, Zhao-Dong; Chen, Li-Wei
Highlights: Proposes a method to derive surface moisture emissivity in unsteady transfer process. The proposed method only requires overall weight of the sample. Moisture emissivity was presented for timber surface with different types of coating. Abstract: Mechanical property and durability of timber members is significantly affected by their surface moisture emissivity which determines the rate they exchange the moisture with the surrounding air. The surface moisture emissivity depends on various parameters including the air flow rate, the temperature and the surface treatment. However, there currently lacks a suitable method for measuring it in the actual working environment of the timber structures. This paper proposes such a method which can identify the surface moisture emissivity factor for timber members with different kinds of surface treatment in their unsteady moisture transfer process. The method is based on Bayesian updating of the numerical model of moisture transfer process of the wood based on the overall weight change. The numerical model considers coupled transfer of the vapour and the bound water. Influences of the sorption hysteresis were also included. Using the method, moisture emissivity factor of different kinds of timber surfaces can be measured by weighting their small-sized samples exposed to ambient climate. Steady moisture transfer process, controlled temperature and RH environment, or the information of the moisture gradient in the samples are not required. Using the method, surface moisture emissivity factor of a pine wood was determined without and with different kinds of surface paint. The measured factor was validated by additional experimental data.